Development and Validation of a Questionnaire to Measure Chinese Preschool Teachers’ Implementation of Social-Emotional Practices - Luo, Li; Snyder, Patricia; Qiu, Yuxi; Huggins-Manley, Anne Corinne; Hong, Xiumin (Frontiers in Psychology, 2021)
We describe the development and validation of the Social-Emotional Teaching Practices Questionnaire-Chinese (SETP-C), a self-report instrument designed to gather information about Chinese preschool teachers' implementation of social-emotional practices. Initially (study 1), 262 items for the SETP-C were generated. Content validation of these items was conducted separately with Chinese practice experts, research experts, and preschool teachers. Significant revisions were made to items based on theoretical evidence and empirical findings from initial content validation activities, which led to a 70-item version of the SETP-C. In study 2, preliminary psychometric integrity evidence and item characteristics of the SETP-C were gathered based on the data from a sample of 1,599 Chinese preschool teacher respondents. Results from confirmatory factor analyses suggested a seven-factor measurement model, and high internal consistency score reliability was documented for each dimension of the SETP-C. Results of item response theory graded response models further indicated adequate psychometric properties at the item level.